PERAN BUZZER DI MEDIA SOSIAL DALAM MEMBENTUK OPINI KEBIJAKAN PUBLIK DI MASYARAKAT PADA PEMILU 2024 - Rahim, Salsabila Nuur; Shabrina, Heldiani Nur; Salsabila, Rey; Hanum, Syarifah; Zemlya, Nabila Ar-Rafa; Rahman, Abdul (Jurnal PubBis, 2024)
The presence of buzzers in the 2024 election has raised concerns due to their potential to spread misinformation, which can lead to disputes and distrust in political issues, including public policy. This situation can cause societal unrest and influence how people think and act. This study aims to understand the role of buzzers on social media in shaping public policy opinion during the 2024 election in Indonesia. The research adopts a qualitative approach, including observations of buzzer activity on social media platforms such as TikTok and X, interviews with public communication and political experts, literature reviews, and social media content analysis. The findings indicate that buzzers have a significant impact on spreading information and shaping public opinion, both positively and negatively, including black campaigns that incite conflict and hate speech. Therefore, serious attention from the government and relevant agencies such as the Indonesian Broadcasting Commission (KPI), along with cooperation between the General Elections Commission (KPU) and the Election Supervisory Board (Bawaslu), is crucial to control the use of social media and ensure the credibility of disseminated information. Strict oversight, comprehensive regulations, and public education on digital literacy are essential to address the negative impacts of buzzer activities. Keywords: Buzzer; Social Media; Public Policy Opinion; 2024 Election